The Behavior of Society in Environmental Cleanliness Care on Gemar MTR Program in Makassar City - Hasyim, Muhammad Azwar; Setyowati, Dewi Liesnoor; Prajanti, Sucihatiningsih Dian Wisika (Universitas Negeri Semarang, 2018)
The trash volume was increased in the city of Makassar, that environmental problems caused by the behavior of the society for less care about the cleanliness of the environment. Therefore, Makassar City Government policy urgently needed to resolve the problems. This research aims to describe and analyze the behavior of environmental cleanliness care in Makassar City Society and the implementation Gemar MTR program to forming behavior of environmental cleanliness care in Makassar Society. This research uses qualitative research methods with the techniques of data collection through interview, observation, and study documents. The results showed that the people of Makassar City have a high understanding of the complexity and environmental impacts, so that the people be able to show their behavior of environmental cleanliness with several efforts such as disposing of waste in the provided places, actively participating in environmental cleaning activities, handling and sorting out the waste correctly through the 3R principle (reduce, reuse, recycle). Furthermore, the implementation of Gemar MTR has been running pretty well, through the active performance of the implementer program in the field, so that these programs can positively impact to forming and improving behavior of environmental cleanliness care in Makassar Society.